2013
DOI: 10.1007/s10508-012-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk and Sexual Orientation: A Critical Review

Abstract: Many studies have reported higher rates of suicide attempts among sexual minority individuals compared with their heterosexual counterparts. For suicides, however, it has been argued that there is no sexual orientation risk difference, based on the results of psychological autopsy studies. The purpose of this article was to clarify the reasons for the seemingly discrepant findings for suicide attempts and suicides. First, we reviewed studies that investigated if the increased suicide attempt risk of sexual min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(80 citation statements)
references
References 77 publications
4
69
0
7
Order By: Relevance
“…An exclusively gay sexual orientation was associated with greater health stress and the presence of suicidal thoughts compared to exclusively heterosexual men. This finding provides additional support for the findings of other studies in which it has been found that same-sex orientation within both men and women is associated with some poorer health outcomes, greater depression, and more suicide than an other-sex orientation (e.g., Boehmer et al, 2012; Collier et al, 2013; Fredriken-Goldsen et al, 2013; Hatzenbuehler et al, 2012; Petterson, VanderLaan, & Vasey, 2016; Ploderl et al, 2013; Rosario et al, 2014; Wichstrom & Hegna, 2003). However, the fact that some stressors were not elevated in gay male adolescents—and even, on some measures, seemed to reflect better adjustment—relative to heterosexual male adolescents also suggests complexity of adjustment, with some sexual minorities having a very good adjustment and a high degree of psychological resilience (e.g., Busseri, Willoughby, Chalmers, & Bogaert, 2006; Rieger & Savin-Williams, 2012; Savin-Williams, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…An exclusively gay sexual orientation was associated with greater health stress and the presence of suicidal thoughts compared to exclusively heterosexual men. This finding provides additional support for the findings of other studies in which it has been found that same-sex orientation within both men and women is associated with some poorer health outcomes, greater depression, and more suicide than an other-sex orientation (e.g., Boehmer et al, 2012; Collier et al, 2013; Fredriken-Goldsen et al, 2013; Hatzenbuehler et al, 2012; Petterson, VanderLaan, & Vasey, 2016; Ploderl et al, 2013; Rosario et al, 2014; Wichstrom & Hegna, 2003). However, the fact that some stressors were not elevated in gay male adolescents—and even, on some measures, seemed to reflect better adjustment—relative to heterosexual male adolescents also suggests complexity of adjustment, with some sexual minorities having a very good adjustment and a high degree of psychological resilience (e.g., Busseri, Willoughby, Chalmers, & Bogaert, 2006; Rieger & Savin-Williams, 2012; Savin-Williams, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…Also, in order to decrease SROs among youths there is a need to improve the negative impression and attitude that society displays towards homosexuals, and a need to establish anti-bullying policies towards LGB youths [28, 34]. On the same note, family-based interventions can decrease hopelessness and depression, thereby leading to less suicide attempts [35]. Countries are obligated to establish policies that reinforce the family’s role to ensure parental love and support towards children and youths [2].…”
Section: Discussionmentioning
confidence: 99%
“…S everal reviews and meta-analyses have summarized the growing body of evidence pointing to higher risk of suicidality among sexual minorities generally and gay men in particular (King et al, 2008;Plöderl et al, 2006Plöderl et al, , 2013. In accordance with the international literature, Swiss findings have shown that a majority of gay/bisexual men reported one or more of the main forms of suicidality-i.e., suicidal ideation, suicide plans, and suicide attempts-in their lifetime, with every sixth man reporting an attempt to end his life (Wang et al, 2012).…”
mentioning
confidence: 92%